2007 IEEE International Conference on Signal Processing and Communications 2007
DOI: 10.1109/icspc.2007.4728462
|View full text |Cite
|
Sign up to set email alerts
|

Computer Aided Detection of Prostate Cancer using Fused Information from Dynamic Contrast Enhanced and Morphological Magnetic Resonance Images

Abstract: This paper presents a computer-aided diagnosis scheme for the detection of prostate cancer. The pattern recognition scheme proposed, utilizes fused dynamic and morphological features extracted from magnetic resonance images (MRIs). The performance of the proposed scheme has been evaluated through extensive training and testing on several patient cases, where the staging of their condition has been previously evaluated by both ultrasoundguided biopsy and radiological assessment. The classification scheme is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…These comparisons are subjective as all metrics are highly influenced by the number of datasets and modalities. For example, the method in [10] produced the lowest sensitivity based on 303 prostates, whereas the method in [12] shows higher accuracy in 10 cases but has not been tested on a larger dataset. The method proposed by Sung et al [2] achieved the best results in all metrics while method proposed by Vos et al [3] achieved similar result in terms of CCR using combination of different modalities (T2-W+DCE).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…These comparisons are subjective as all metrics are highly influenced by the number of datasets and modalities. For example, the method in [10] produced the lowest sensitivity based on 303 prostates, whereas the method in [12] shows higher accuracy in 10 cases but has not been tested on a larger dataset. The method proposed by Sung et al [2] achieved the best results in all metrics while method proposed by Vos et al [3] achieved similar result in terms of CCR using combination of different modalities (T2-W+DCE).…”
Section: Resultsmentioning
confidence: 82%
“…As a result, the probability of cancerous tissues being missed is higher (false negatives). Therefore, the ultimate goal of our research is to develop Computer Aided Diagnosis (CAD) tools for prostate cancer detection by segmenting area (in our case a sub region) which has the highest probability being malignant, hence could help clinicians to perform targeted biopsies and have the potential to improve the accuracy of clinical diagnostic tests [12]. Figure 1 shows an example of prostate gland with random biopsies which represents the current scenario of biopsy tests.…”
Section: Introductionmentioning
confidence: 98%
“…Sham et al , developed a decision support system that used SVM to generate cancer probability maps from multiparametric MR images, and Niaf et al , reported that SVM produced the best result based on a comparison study of four different supervised learning methods (SVM, linear discriminant analysis, k ‐nearest neighbors, and naive Bayes classifiers) based on a feature set derived from gray‐level images such as first‐order statistics, Haralick features, and gradient features. This was followed by a study in , which is 2% below the best performance (and 1% above the result of our proposed method) in Table . Ampeliotis et al , used probabilistic neural networks to classify a set of feature vectors extracted from T2‐W morphological images and T1‐W DCE.…”
Section: Discussionmentioning
confidence: 86%
“…This was followed by a study in , which is 2% below the best performance (and 1% above the result of our proposed method) in Table . Ampeliotis et al , used probabilistic neural networks to classify a set of feature vectors extracted from T2‐W morphological images and T1‐W DCE. Other methods achieved more than 80% accuracy.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, for classification tasks, we observed the use of classifiers such as k-nearest neighbor (Filipczuk et al, 2013;Gedik and Atasoy, 2013;Gopinath and Shanthi, 2013;He et al, 2011;Muramatsu et al, 2013;Nava et al, 2014;Odeh et al, 2006;Osman et al, 2009;Raja et al, 2010;Verikas et al, 2006), artificial neural networks (Barhoumi et al, 2007;Geetha et al, 2008;Jasmine et al, 2009;López et al, 2008;Raja et al, 2007;Streba et al, 2012;Verma, 2009;Wu et al, 2006), Bayesian classifiers (Ampeliotis et al, 2007;Bhooshan et al, 2011;Garnavi et al, 2012;Gruszauskas et al, 2008Gruszauskas et al, , 2009Retter et al, 2013;Tolouee et al, 2011) techniques based on linear discriminant analysis (Lee et al, 2009;Muramatsu et al, 2013;Tanner et al, 2006) and logistic regression models (Shen et al, 2007;Tanner et al, 2006).…”
Section: Tasks For Computer-aided Diagnosis Systemsmentioning
confidence: 99%